Bibliometric Analysis of Characteristics and Trends in Technical and Vocational Education and Training (TVET) - Yanuar Agung Fadlulullah; Wagiran Wagiran; Nurhening Yuniarti; Muhamad Riyan Maulana; Arya Yusuf (Journal of Educational Sciences, 2026)
Technical Vocational Education and Training (TVET) plays a crucial role in enhancing workforce competitiveness in Indonesia by equipping individuals with skills relevant to industry needs. However, the system faces challenges in adapting its curriculum to technological advancements and an increasingly digital economy. This study aims to map the trends, challenges, and developments in TVET through a bibliometric analysis of publications from 2015 to 2025, using data from Scopus and the R Studio analysis tool. The study found a significant rise in TVET-related publications, particularly from 2021 to 2024, with an annual growth rate of 20.08%. Key themes identified include competency frameworks, digital competencies, and the integration of technologies like artificial intelligence. These findings point to a shift towards technology-driven vocational education, which is essential to meet global job market demands. The study also emphasizes the importance of international collaboration to enhance TVET quality and relevance. The insights from this research can guide policymakers and educators in designing curricula that are more adaptable to industrial and technological changes. Thus, TVET must evolve with a focus on developing digital skills and industry-based competencies to prepare a workforce capable of tackling future challenges.